AN SCIENTIFIC ANALYSIS ON JAPAN’S TECHNOLOGY PROGRESS AND SUCCESS AND HOW COVID -19 HAS AFFECTED THE ECONOMIC GROWTH OF THE THIRD LARGEST ECONOMY - Dr.Sumanta Bhattacharya; Dr. Jayanta Kumar Ray; Shakti Sinha; Bhavneet Kaur Sachdev (Galaxy International Interdisciplinary Research Journal, 2021)
Japan - the third largest economy in the world has shrank due to the COVID-19 pandemic , the first financial crisis ever since 2009 , Japan economy is heavily depended on export and foreign demand , along with tourism . The sudden lockdown brought the economy of Japan a stand still. On the other hand the decreasing population of Japan has an impact on the economic growth , it is believed that the country would soon become an home for old men and women. Japan has a low birth rate and people avoid marriages . Japan leads the world when it comes to technology. Japan has the fastest train in the world , with excellent rail and road connectivity , there have a good and healthy lifestyle where we find a massive ageing population exiting in Japan where above 90% of the population live in the urban area . Japan is also working towards renewable energy and aims to product zero emission energy by 2050 . It has also emerged as a powerful superpower in Japan . The country is prone to earthquake and experiences 3 to 4 earthquake small and minor per day . However with its technology advancement it has been able construct earthquake tolerant buildings .Japan is regarded as the future of the world with its innovative ideas and techniques . it is far ahead of other countries when it comes to innovation and development .